Challenges in Posing HOTS-Oriented Problems: A Study of Prospective Mathematics Teachers with Restricted Creativity - Rahayu, Dwi Shinta; Resti, Nalsa Cintya; Pebriyanti, Putri (Faculty of Tarbiyah, Institut Agama Islam Negeri (IAIN) Kediri, Indonesia, 2025)
The ability to pose problems that require Higher Order Thinking Skills (HOTS) is a crucial competency for prospective mathematics teachers. However, numerous prospective teachers still experience difficulties in constructing mathematics HOTS-oriented problems, especially those with restricted creativity. This qualitative research aims to explore the difficulties experienced by prospective teachers with low levels of creativity in posing HOTS-oriented mathematics problems. This research is an extension of prior investigation that categorized 85 prospective teachers into five levels of creativity, revealing that more than 40% fell into the less creative and non-creative categories. This research data was collected through documentation of problem-posing tasks from previous research and in-depth interviews. Data was analyzed using a thematic approach to identify emerging patterns of difficulty. The result revealed four main categories of difficulty: (1) difficulty posing problems with varying cognitive levels, (2) difficulty posing more than one HOTS problem, (3) inability to pose problems at the HOTS level, and (4) difficulty posing solvable problems. The most dominant difficulty was in the aspect of cognitive level variation. These findings indicate that creativity plays a significant role in the ability to pose HOTS-oriented problems. This research suggests the need to develop targeted pedagogical interventions to support creative thinking processes and question design skills in prospective teacher education).